A Software Product Line Design Based Approach for Real-time Scheduling of Reconfigurable Embedded Systems. (February 2021) - Gharsellaoui, Hamza; Maazoun, Jihen; Bouassida, Nadia; Ahmed, Samir Ben; Ben-Abdallah, Hanene
Abstract: In this paper, we deal with the development of dynamically reconfigurable embedded systems in terms of the production of execution schedules of system tasks (feasible configuration) under hard real-time constraints. Indeed, several real-time embedded systems must be dynamically reconfigured to account for hardware/software faults and/or maintain acceptable performances. Depending on the run-time environment, some reconfigurations might be unfeasible, i.e., they violate some real-time constraints of the system. More specifically, we propose an approach that starts from a set of reconfigurations to construct a Software Product Line (SPL) that can be reused in a predictive and organized way to derive real-time embedded systems. To make sure that the SPL offers various feasible reconfigurations, we define an intelligent agent (IA) that automatically checks the system's feasibility after a reconfiguration scenario is applied on a multiprocessor embedded system. This agent dynamically determines precious technical solutions to define a new product whenever a reconfiguration is unfeasible. The set of products thus defined by the agent can then be unified into an SPL. The originality of our approach is its capacity to extract, from the unfeasible configurations of an embedded system, an SPL design enriched with real-time constraints and modeled with a UML Marte profile. The SPL design can assist in the comprehension, reconfiguration as well as evolution of the SPL in order to satisfy real-time requirements and to obtain a feasible system under normal and overload conditions. Highlights: Highly real-time reconfigurable scheduling of embedded systems. The implementation of an Intelligent Agent that checks the system's feasibility. The Intelligent Agent provides precious technical solutions by defining new SPL. The proposed approach extracts from the unfeasible embedded system the SPL design. Enriched SPL is modeled with UML Marte profile that assists in its comprehension.